Thomas D. Davis, The Code of the City of Lynchburg, Va., Containing the Charter of 1880, with the Amendments of 1884, 1886 and 1887, and the General Ordinances in Force July 1st, 1887, Also a Digest of Acts of Assembly and of Ordinances Affecting the Rights and Interests of the City of Lynchburg and its Citizens, Together with a Brief Sketch, Historical and Statistical, at 117, ch. 19, § 19 (1887) - (:unkn) unknown (My University, 1887)
No person shall carry gunpowder, blasting powder, dynamite or other explosives on a vehicle in any part of the city unless the same shall be secured in kegs, boxes, or canisters, so that no part thereof can fall out or escape.
Keywords: GUNPOWDER - TRANSPORTATION